2021
DOI: 10.1007/s10342-021-01373-0
|View full text |Cite
|
Sign up to set email alerts
|

Forest inventory-based assessments of the invasion risk of Pseudotsuga menziesii (Mirb.) Franco and Quercus rubra L. in Germany

Abstract: In Europe, some non-native tree species (NNT) are classified as invasive because they have spread into semi-natural habitats. Yet, available risk assessment protocols are often based on a few limited case studies with unknown representativeness and uncertain data quality. This is particularly problematic when negative impacts of NNT are confined to particular ecosystems or processes, whilst providing valuable ecosystem services elsewhere. Here, we filled this knowledge gap and assessed invasion risks of two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…In addition, repeated inventories can be used to determine how the state of NNT is developing over time. Such data can be derived from regional and national forest inventories (NFI), regional datasets covering protected areas (e.g., Bindewald et al, 2021 ; Oswalt et al, 2015 ; Steinmetz & Bauhus, 2016 ; Verheyen et al, 2007 ; Wagner et al, 2017 ), or from assessment reports of habitats valuable for nature conservation (e.g., EU Habitats Directive, Campagnaro et al, 2018 ). However, the usefulness of this method is limited to NNT that have already reached a certain distribution (Klemmt & Neubert, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, repeated inventories can be used to determine how the state of NNT is developing over time. Such data can be derived from regional and national forest inventories (NFI), regional datasets covering protected areas (e.g., Bindewald et al, 2021 ; Oswalt et al, 2015 ; Steinmetz & Bauhus, 2016 ; Verheyen et al, 2007 ; Wagner et al, 2017 ), or from assessment reports of habitats valuable for nature conservation (e.g., EU Habitats Directive, Campagnaro et al, 2018 ). However, the usefulness of this method is limited to NNT that have already reached a certain distribution (Klemmt & Neubert, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, concern has been expressed that red oak competes with native tree species in semi‐natural oak forests in Germany (Nehring et al, 2013 ). Although a recent study showed that red oak has spread into certain protected oak forest communities in southwest Germany, there is still insufficient data on the stage of establishment and the actual (long‐term) impacts on biodiversity in these sensitive ecosystems to draw firm conclusions, for example, on its competitiveness (Bindewald et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the introduced tree species in Poland originate from North America (McDowell et al 2000) and Asia, and some from Europe (Szymanowski 1959, Białobok and Chylarecki 1965, Bellon et al 1977, Feliksik and Wilczynski 2003, St Clair et al 2005), e.g. Italy (Marziliano et al 2015, Ravaioli et al 2019, Marchi and Cocozza 2021, Germany (Marziliano et al 2015, Bindewald et al 2021, and Poland (Giedrowicz et al 2020).…”
Section: Introductionmentioning
confidence: 99%